Coping Experiences of Nigerian Women during Pregnancy and Labour: A Qualitative Study - Deborah Esan; Janet Adugbo; Israel Fawole; Oluwadamilare Akingbade (Shiraz University of Medical Sciences, 2023)
Background: Pregnancy and labour are defining moments in the lives of women. While these are joyful moments for many, some physical and psychological issues have been reported during labour and pregnancy. This study was conducted to explore the coping experiences of Nigerian women during pregnancy and labour.Methods: This is an exploratory qualitative study using the content analysis. The study was conducted from November 2021 to January 2022 in Ekiti State and Federal Capital Territory, Nigeria. In-depth interviews were conducted with 30 women selected using the purposive sampling technique. Data collection was stopped when we reached data saturation. Data were analyzed through content analysis using the NVIVO software version 12.Results: Two themes emerged from the study including coping strategies during pregnancy and trying to endure labour pain. The theme, coping strategies utilized during pregnancy, included obtaining the relatives' experiences, seeking information, religious practices, and engaging in exercise. The theme,  trying to endure labour pain, consisted of exercising for pain relief, relying on God, Positive imagination, giving psychological support, and behaving according to the accepted cultural beliefs.Conclusion: Findings suggested that women utilized many non-pharmacological methods for coping. Interventions to support women during pregnancy and labour should consider these strategies during planning and implementation.